First observation of edge impurity behavior with n = 1 RMP application in EAST L-mode plasma - Zhang, Wenmin (2024)
High-Z impurity accumulation suppression and mitigation in core plasma is frequently observed in EAST edge localized mode mitigation experiments by using resonant magnetic perturbations (RMP) coils. To study the individual effects of the RMP field on impurity transport, based on high-performance extreme ultraviolet impurity spectroscopic diagnostics, the effect of the n = 1 (n is the toroidal mode number) RMP field on the behavior of intrinsic impurity ions at the plasma edge, e.g. He+, Li2+, C2+–C5+, O5+, Fe8+, Fe15+, Fe17+, Fe22+, Cu17+, Mo12+, Mo13+ and W27+, is analyzed for the first time in L-mode discharges. Based on the evaluation of the location of these impurity ions, it is found that with the increase in RMP current (IRMP), an impurity screening layer inside the last closed flux surface is formed, e.g. at ρ = 0.74–0.96, which is also the region that the RMP field affects. Outside this screening layer, the impurity ion flux of He+, Li2+, C2+, C3+, O5+, Fe8+, Mo12+ and Mo13+ ions increases gradually, while inside this screening layer, the impurity ion flux of C4+, C5+, Cu17+, W27+, Fe15+, Fe17+ and Fe22+ ions decreases gradually. When IRMP is higher than a threshold value, RMP field penetration occurs, accompanied with m/n = 2/1 mode locking, and the position of this screening layer moves to the plasma core region, i.e. ρ = 0.66–0.76, close to the q = 2 surface, and the opposite behavior of the impurity ion flux at two sides of the screening layer is strengthened dramatically. As a result, significant decontamination effects in the plasma core region, indicated by the factor of ((ΓImpZ+)w/o–(ΓImpZ+))/(ΓImpZ+)w/o (where (ΓImpZ+)/(ΓImpZ+)w/o denotes the impurity ion flux ratio with and without RMP), is observed, i.e. 30%–60% for heavy impurity (Fe, Cu, Mo, W), and ∼27% for light impurity of C. In addition, the analysis of the decontamination effects of C and Fe impurities under four different RMP phase configurations shows that it may be related to the strength of the response of the plasma to RMP. These results enhance the understanding of impurity accumulation suppression by the n = 1 RMP field and demonstrate a candidate approach using RMP coils for W control in magnetic confinement devices.